Association of Omega-3 Index and Blood Cell Count-Derived Systemic Inflammatory Indexes among Testicular Germ Cell Tumor Survivors - Milica Zeković; Marko Živković; Marija Takić; Sanja Stanković; Nebojša Bojanić; Aleksandar Janičić; Uroš Bumbaširević (Proceedings)
Background and objectives: Although testicular cancer is considered the paradigm of highly curable malignancy, treatment-induced adverse effects and potential impairment of gonadal function may cause non-negligible long-term health repercussions, including metabolic disturbances and cardiovascular sequelae. This observational, cross-sectional study recruited a sample of testicular germ cell tumor survivors (TGCTSs) attending routine follow-up care, with the aim to investigate the relationship between the Omega-3 Index, a promising cardiometabolic risk-assessment biomarker, and complete blood cell (CBC) count-derived systemic inflammation indexes. Methods: Erythrocyte membrane fatty acid (FA) profiling was performed by gas chromatography with flame ionization detection. The Omega-3 index (OI3) was computed by summarizing eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) expressed as a percentage of total FAs. Inflammatory indexes, including NLR (neutrophil-to-lymphocyte ratio), SII (systemic immune-inflammation index (platelet count × NLR)), SIRI (systemic inflammatory response index (monocyte count × NLR)), and AISI (aggregate index of systemic inflammation (monocyte count × SII)) were determined using routinely obtained hematological parameters. Results: In the analyzed cohort (n = 92, age <semantics><mover>x̄</mover></semantics> = 35.89 ± 8.67 years), the mean value of O3I was 4.41 ± 0.92%, where 53.26% of men were allocated the high-risk group (O3I < 4%) and the rest were in the moderate cardiovascular hazard category (4% ≤ O3I < 8%). The O3I correlated inversely with the NLR, SII, and AISI (r = −0.234, −0.241, and −0.249, respectively, all p < 0.01). A negative association was determined between the total content of polyunsaturated fatty acids and SIRI (r = −0.221, p < 0.05). The NLR and AISI were statistically significantly lower in the subgroup of patients with O3I ≥ 4% (p < 0.05). Discussion: Blood cell count-based inflammatory indexes may contribute to a more efficient risk stratification of TGCTS in relation to cardiometabolic disorders. Further large-scale research and long-term intervention trials are warranted to investigate the clinical significance of an increased intake of anti-inflammatory long-chain omega-3 polyunsaturated FA via dietary sources and/or supplementation in modulating the inflammatory process and reducing the morbidity burden in this patient population.